Relevance of subclinical right ventricular dysfunction measured by feature-tracking cardiac magnetic resonance in non-ischemic dilated cardiomyopathy. (3rd October 2022) - Pozo Osinalde, E; Urmeneta Ulloa, J; Cabrera, J A; Martinez De Vega, V; Thuissard, I J; Andreu-Vazquez, C; Perez De Isla, L; Marcos-Alberca, P; Cabeza, B; Rodriguez-Hernandez, J L; Luaces Mendez, M; Gomez De Diego, J J; et al.
Abstract: Background: Right ventricular (RV) dysfunction is associated with worse prognosis in non-ischemic dilated cardiomyopathy (NIDCM). Cardiac magnetic resonance (CMR) is considered the gold standard for RV evaluation. However, scarce data is available with the new feature tracking (FT) technique, which allows strain evaluation from conventional cine sequences. Purpose: Our aim is to analyze the prognostic relevance of RV myocardial deformation measured by FT-CMR in NIDCM. Methods: Consecutive patients with NIDCM diagnosis and CMR at diagnosis were retrospectively included. Global longitudinal strain of RV free wall (GLS-RVFW) and fractional area change (FAC) were obtained from standard CMR cine sequences with a dedicated FT software. Their association with a composite endpoint (heart failure admission, implantable cardioverter defibrillator in secondary prevention, and death) was evaluated using a logistic regression model. Results: FT derived strain was obtained in 98 patients (68±13 years, 71.4% males) with NIDCM, mostly idiopathic (75.5%). Although our cohort showed a severely impaired left ventricular systolic function (LVEF = 29.5±9.6%, 47% with LVEF ≥30%) the RV function was relatively preserved on average (RVEF 52.2±14.6%, 72% with RVEF ≥45%). During a 3.2 [2.2–4] years follow-up 26.5% presented at least one admission for heart failure (HF), 5.1% received an implantable cardioverter defibrillator in secondary prevention, and 8% died. There was no association of RV-FT parameters with prognosis considering the entire study population. However, in patients with LVEF ≥30%, admissions for HF were associated with worse values of GLS-RVFW (−21.6±6.6% vs −31.3±10%; p=0.006) and FAC (32.8±15.8% vs 47.5±13.9%; p<0.001). Similar differences were observed when only patients with RVEF >45% were considered. An GLS-RVFW cut-off point of −19.5% and FAC of 36.5% showed good prognostic performance. Decreased GLS-RVFW or FAC represented an independent predictor for the composite endpoint in patients with LVEF ≥30%. Conclusions: In our series of NIDCM decreased values of GLS-RVFW or FAC were able to predict major events independently of RVEF in the subgroup of patients without severe LV dysfunction. Therefore, RV deformation parameters by FT may be early markers of poor prognosis in NIDCM. Funding Acknowledgement: Type of funding sources: None.